Effectiveness of Beetroot (Beta Vulgaris L) Extracts On Blood Pressure Level Among Postpartum Mothers With Hypertension - Merisa Restiani Arma; Ta'adi Ta'adi; Sri Sumarni (Universitas STRADA Indonesia, 2020)
Hypertension is the most medical problem encountered in pregnancy to postpartum period and remains one of the most causes of maternal death. High nitrate content of beetroot as well as potassium and flavonoids of celery may lower blood pressure. This study investigate the effectiveness of beetroot extracts on reducing blood pressure postpartum mothers with hypertension. The study was a Quasy-experimental control group pre-posttest design. A total sample of 30 postpartum mothers with hypertention was enrolled in the study and randomly assigned in 2 groups. The consumption of beetroot extract decreased systolic BP 27,40 and diastolic 13,47. Meanwhile in CG, BP was reduced by 8,40 for systolic and 10,53 for diastolic. There was a difference in mean decrease systolic BP between the intervention and control group (p<0.05), there was no differences in mean diastolic BP (p>0.05). Beetroot extract effective reducing blood pressure postpartum mother with hypertension without worrying about side effects.